2019
DOI: 10.1145/3213769
|View full text |Cite
|
Sign up to set email alerts
|

Toward Universal Spatialization Through Wikipedia-Based Semantic Enhancement

Abstract: This article introduces Cartograph, a visualization system that harnesses the vast world knowledge encoded within Wikipedia to create thematic maps of almost any data. Cartograph extends previous systems that visualize non-spatial data using geographic approaches. Although these systems required data with an existing semantic structure, Cartograph unlocks spatial visualization for a much larger variety of datasets by enhancing input datasets with semantic information extracted from Wikipedia. Cartograph's map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…We showed that synthetic navigation sequences from the public clickstream dataset are effective for many practical applications for all 8 considered languages. We compared the performance of real and synthetic navigation sequences in four different downstream tasks involving the use of navigation sequences ( link prediction [46], next-article prediction [12], generating representations [60], and topic classification [35]), revealing that using clickstream data often yields performance that are within 10% (or less) in comparison to using real navigation sequences (Table S2). Specifically, article embeddings generated from synthetic navigation sequences are of comparable quality to those generated from real navigation sequences.…”
Section: Discussion and Concluding Insights 71 Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that synthetic navigation sequences from the public clickstream dataset are effective for many practical applications for all 8 considered languages. We compared the performance of real and synthetic navigation sequences in four different downstream tasks involving the use of navigation sequences ( link prediction [46], next-article prediction [12], generating representations [60], and topic classification [35]), revealing that using clickstream data often yields performance that are within 10% (or less) in comparison to using real navigation sequences (Table S2). Specifically, article embeddings generated from synthetic navigation sequences are of comparable quality to those generated from real navigation sequences.…”
Section: Discussion and Concluding Insights 71 Summary Of Resultsmentioning
confidence: 99%
“…Paranjape et al [46] showed that navigation traces provide a strong signal to predict new useful links among Wikipedia articles. Furthermore, reading sessions can be used to construct article embeddings-where similarity captures articles that are read in close succession [75]-that have been used for building alternative visual representations of the semantic space of Wikipedia [60]. Applications of clickstream data.…”
Section: Related Workmentioning
confidence: 99%
“…Sen et al . [SSL*17, SSL*19] add virtual “water points” to the visualization for generating “water” regions not encircled by the Voronoi mesh for low‐density parts on the spatialized data. In R‐Map [CLCY20] and E‐Map [CCL*17, CCA*18], an initial force‐directed layout is used to compute a Voronoi mesh on graph data.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Cartograph [SSL*19] for example uses the pin symbol to indicate the location of a data item, similar to digital maps (see Figure 5a). While the symbol also resembles the signal poles used in American football, their wide‐spread use to indicate locations in digital maps makes them recognizable as such for point‐based imitation.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation